Demystifying content complexity: The role of augmented reality in interactive learning (International Seven Journal of Multidisciplinary, 2023)
he integration of augmented reality (AR) in education represents a promising frontier for facilitating the teaching and learning of potentially complex content. This study explores how AR can be used to transform didactic abstractions into interactive experiences with the aim of promoting deeper understanding. Improves knowledge retention in areas such as precision science and biology. The methodology used includes the analysis of documented experiences and the compilation of empirical results relating to the use of AR in educational environments. The results suggest that AR not only engages students in their learning through innovative forms of educational content, but also improves students' understanding by providing a three-dimensional and interactive perspective on the concepts learned. In this way, AR resources overcome traditional barriers and emerge as a new educational language. However, with the aim of sustainable and integrated applicability of this technology, there is a need for continuous development and in-depth research to ensure the effectiveness and ethical integration of this technology in learning environments.